Trends and hotspots in cupping therapy research for pain: a bibliometric study - Xu, Renjie; Liu, Shi-Lu; Xu, Guangxu; Yan, Chengjie; Cui, Qi; Liu, Shan; Sun, Mingliang (Frontiers in Medicine, 2025)
BackgroundCupping therapy (CT), a traditional form of alternative medicine, has gained attention as a non-pharmacological intervention for pain. Its applications span various pain-related conditions such as musculoskeletal disorders, migraines. Despite its growing popularity, comprehensive analyses of research trends, collaboration networks, and emerging hotspots in CT for pain remain limited.MethodsThis bibliometric study analyzed 234 publications on CT for pain sourced from the Web of Science Core Collection. CiteSpace and VOSviewer software, and Bibliometric analysis website were employed to analyze trends, identify key contributors, and map global collaboration networks. Co-cited references, keyword clustering, and burst detection analyses were performed to uncover research hotspots and trends.ResultsA total of 234 publications from 31 countries and 437 institutions were included. China led in publication volume, while the United States had the highest total citations. The Korea Institute of Oriental Medicine and the University of Duisburg-Essen were identified as central hubs for institutional collaboration. High-frequency keywords such as “pain,” “cupping therapy,” “acupuncture,” and “negative pressure” highlighted a focus on CT’s clinical applications and mechanisms. Emerging trends included the integration of CT with modalities like acupuncture and physical therapy. However, methodological limitations, such as inconsistent protocols and insufficient mechanistic studies, were identified as key challenges.ConclusionThis study offers an overview of the research landscape for CT in pain management, its potential as a safe and effective therapy. To strengthen its role in evidence-based medicine, future research should focus on standardizing treatment protocols, conducting high-quality clinical trials, and exploring its underlying mechanisms.